Allocation and optimization of carbon emission permits considering fairness and efficiency under the dual-carbon background - Xiao, Yong; Wu, Leyou; Xie, Pinjie; Pan, Xianyou (Frontiers in Environmental Science, 2022)
Reasonable and effective allocation of carbon emission permits is one of the important tasks to achieve the goal of carbon neutrality. Based on the difference in carbon emission reduction contribution and capability of the industries, this paper proposes a carbon emission permits allocation and optimization scheme that take into account fairness and efficiency. First, based on fairness principle, establish a carbon emission quota system of the six industries and determine the index weights, and use the comprehensive index method to realize the initial allocation of carbon emission permits. Then, on the basis of evaluating the initial carbon emission permits allocation efficiency, based on efficiency principle, the zero sum gains data envelopment analysis (ZSG-DEA) model is used to iteratively obtain the optimal allocation scheme of carbon emission permits. Example analysis shows that the carbon permit allocation and optimization model based on fairness and efficiency principles proposed can realize the optimal allocation of industrial carbon emission permits, ensure the optimal efficiency of industrial carbon permit allocation, and provide adequate support for the carbon emission reduction decisions of the six industries.